Washing Reagents for Remediating Heavy-Metal-Contaminated Soil: A Review - Zhang, Heng; Xu, Yongxin; Kanyerere, Thokozani; Wang, Yang-shuang; Sun, Minhui (Frontiers in Earth Science, 2022)
Heavy-metal pollution of soils becomes a major environmental concern around the world presently. Soil washing provides an effective measure of removing contaminants from soil permanently, of which washing reagent plays a vital role in the process. This paper reviews the current knowledge acquired on the main aspects concerning washing reagents of soil washing for remediation of heavy-metal contaminated soil based on more than 150 published studies over a period from 1990 to 2021. The review identifies and discusses the types of the washing reagents with their associated characteristics. Based on the factors influencing washing remediation, multi-criteria decision-analysis, together with an integrated four-step procedure, is put forward to manage the selection and prioritizing of washing reagents. It crops out from the literature survey that the selection of the washing reagents is a balanced process by taking consideration of washing effect, environmental impact and cost effectiveness. On the basis of such observation and evaluation, it is recommended that further study should be focused on developing of new washing reagents or compound washing reagents that possess the advantage over heavy-metal removal ability, eco-friendliness and cost effectiveness as well. Selecting washing agents that are capable of being recovered from waste such as dissolved organic matter would be a promising trend in washing remediation. Artificial intelligence is expected to assistant the selection of washing reagents.